2009
DOI: 10.1111/j.1467-8535.2008.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐based and computer‐based concept mappings: The effects on computer achievement, computer anxiety and computer attitude

Abstract: The purpose of this paper is to compare the effects of paper-based and computer-based concept mappings on computer hardware achievement, computer anxiety and computer attitude of the eight grade secondary school students. The students were randomly allocated to three groups and were given instruction on computer hardware. The teaching methods used for each group were the conventional method, paper-based concept mapping and computerbased concept mapping. At the end of a 4-week instruction, posttests were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
(43 reference statements)
4
30
0
2
Order By: Relevance
“…As can be observed from the participants' perceptions, this study reveals that CM can facilitate such processes, which, in turn, as shown by the regression analysis, is associated with student achievement. Similar findings were reported in previous research studies on various subjects (Asan, 2007;Chiou, 2008;Erdogan, 2009;Kwon & Cifuentes, 2007;Liu, Chen & Chang, 2010;Schaal, 2010). Therefore, teacher educators should try to provide pre-service teachers with more opportunities of constructing concept maps in their pedagogical courses.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As can be observed from the participants' perceptions, this study reveals that CM can facilitate such processes, which, in turn, as shown by the regression analysis, is associated with student achievement. Similar findings were reported in previous research studies on various subjects (Asan, 2007;Chiou, 2008;Erdogan, 2009;Kwon & Cifuentes, 2007;Liu, Chen & Chang, 2010;Schaal, 2010). Therefore, teacher educators should try to provide pre-service teachers with more opportunities of constructing concept maps in their pedagogical courses.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the results recommend that the CM strategy can also be integrated successfully into teacher education programs in which students do not have prior experience with CM and access to computers. Consistently, former studies revealed that both paper-based and computer-based CM methods produced positive effects on concept learning and attitudes toward CM, but there were no significant differences between the two methods (Erdogan, 2009;Hsieh & Cifuentes, 2006). This research reveals crucial practical implications for future implementations of CM.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Compared with the traditional paper-and-pencil concept mapping approach, computer-based concept maps are more user-friendly and can be more easily corrected (Erdogan, 2009). The use of computer-based concept maps benefits teachers and learners due to the following characteristics: (1) ease of use and making corrections: nodes can be quickly added, corrected, and deleted in computer-based concept mapping, and, guided by simple instructions, users can adjust the concept map structure to make it more visually clear; (2) ease of communication with peers: learners can obtain clear information by displaying their concept maps on the screen and through discussion with others; (3) support for multiple resources: computer-based concept mapping can offer feedback, evaluation, and map history functions, as well as collaborative online tools for map composition (Chiou, Lee, Tien, & Wang, 2017).…”
Section: Computer-based Concept Map Instruction For Learningmentioning
confidence: 99%